Advancements in the field of personality development. Issue 5 (1st May 2014) - De Fruyt, Filip; Van Leeuwen, Karla
ABSTRACT: A summary is provided what the fields of personality and developmental psychology had to offer each other the past decade, reflected in the eleven contributions enclosed in this special issue. Strengths and opportunities to further advance the field are identified, including the extension of general trait with maladaptive trait models, the use of alternative methods to assess personality, and the adoption of configural approaches to describe traits in individuals, beyond more traditional person‐centered approaches.